Cohort Profile Update: The Harmonised Cognitive Assessment Protocol Sub-study of The Irish Longitudinal Study on Ageing (TILDA-HCAP) - Oto, Gabriela; Kenny, Rose; Feeney, Joanne; Monaghan, Ann; Mc Garrigle, Christine (My University, 2025)
The Irish Longitudinal Study on Ageing—Harmonised Cognitive Assessment Protocol (TILDA-HCAP) is closely harmonized with the original Health and Retirement Study (HRS), The Northern Ireland Cohort longitudinal study of Ageing- and The English Longitudinal Study of Ageing HCAPs. TILDA-HCAP was carried out between 2021 and 2024, and included 1344 respondents and 982 informants. Detailed cognitive assessments were carried out in randomly selected respondents aged ≥65 years from The Irish Longitudinal Study on Ageing (TILDA) to provide a composite cognitive assessment that was appropriate for a research diagnosis of dementia and cognitive impairment. TILDA is unique among the HRS family of studies in its collection of objective cardiovascular, autonomic, neuropsychological, and sensory data. Linking HCAP to these data will enhance the understanding of risk factors and biomarkers of cognitive impairment and dementia. Pseudonymized TILDA data sets are available in public data archives, with TILDA-HCAP data forthcoming. All queries about data access should be addressed to tilda@tcd.ie
PUBLISHED
doi:https://doi.org/10.1093/ije/dyaf008
Keywords: aging, cognition, cohort, dementia, longitudinal, older adult; Ageing